Higher Education Leadership Training: Global Maps and Gaps - Rumbley, Laura; van't Land, Hilligje; Becker, Juliette (International Higher Education, 2018)
Globally, most higher education leaders, managers, and policymakers receive no formal/specialized training for their work. Compared to the need, there is a relatively small number of structured training opportunities that exist to build leadership and management capacity in higher education around the world. These training programs are almost universally small in scale and largely unable to offer systematic accounts of the long-term impact of their efforts. This is a critical concern in the face of the myriad opportunities and imperatives facing higher education institutions and systems worldwide—particularly in low-income and emerging economy contexts—now and into the foreseeable future.